PENGARUH VARIABILITAS PERSEDIAAN, UKURAN PERUSAHAAN DAN INTENSITAS PERSEDIAAN TERHADAP PEMILIHAN METODE PENILAIAN PERSEDIAAN (Studi Empiris Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2014-2017) - Erwin Febriansyah; Ade Tiara Yulinda; Lina Rosalinda (UNIVED Press, 2020)
Erwin Febriansyah, Ade Tiara Yulinda, Lina Rosalinda; This study purposes to determine the effect of inventory variability and intensity, company size, on the selection of inventory assessment method. This research examined four independent variables namely inventory variability and intensity, companies size, its dependent variable was the FIFO method and the average method. Type of this research was quantitative research by using secondary data. Research population was all manufacturing companies listed on the Indonesia Stock Exchange of the 2014-2017. The sampling technique used purposive sample, with criteria and selected 41 unit analysis companies to be samples and multiplied by the number observation period are obtained 164 samples (41 companies x 4year). The method for data analysis used logistic regression by using SPSS 18.0. There were four research hypotheses; to examine the effect of inventory variability and intensity, companies size on the selection of inventory assessment methods. The result of study showed that inventory variability, companies size, do not affect on the selection of inventory valuation method. Meanwhile, intensity inventory affects the selection of inventory valuation methods and inventory variability and intensity, companies size together influence the selection of inventory valuation methods. Keywords: Inventory Variability, Company Size, Inventory Intensity, FIFO, Average